A rare incident of Paget's disease of bone in early adult life - Rai, Harishchandra (Medknow Publications & Media Pvt Ltd, 2014)
Paget's disease of bone (PDB) is characterized by a focal alteration of bone remodeling, which leads to bone with anomalous structure and altered mechanical properties associated with pain and complications. It is more common in Western Europe where as rare in Africa and Asia. The disease is more common in men of older adults and mean age of occurrence is 59 ± 14 years. But it is rarely encountered in patients younger than 40 years of age.